The Effect of Proposed Exercises in developing the concentration for the team Of Young for the National Center of Caring The Boxing talented Sport - Abbas, ElafRabeea (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research:Boxing is one of the opening space games that has quick and many influences, as well as being considered a sudden one that was unknown before, that leads to great concentration and the accurate attention of the boxer himself for these effects in order to achieve the kinetic duty in a very short time. Whenever the boxer has high, quick, and great concentration, he will have the ability to defend himself against the fast and sudden parapets of the competitive boxer, as well as to make counter boxes in an inaccurate and fast manner.The problem of the research:Despite the many serious attempts that have been done in the field of developing and promoting the sound and the correct training in the space of boxing, actually, there are many problems that are live up to now. These problems need solutions that are based on a scientific basis that aims to realize the best levels for the boxers, privately, the young boxers.The researcher has noticed through the field experiment, as he is one of the Iraqi champions in the field of boxing, that many of the young boxers have very clear weaknesses in coordination and/or dominance between reactions and the boxes, which need high efficiency in the neuro system and the muscular system.The researcher, furthermore, has mentioned the lack of some coaches using their own training methods for many exercises that are based on great concentration and attention so as to recognize and know the sound and the correct solutions.The aims of this research:Preparing proposed exercises for the purpose of developing the concentration and attention, as well, for the Young Team in the National Center for caring for the talented boxers.Conclusions:1. Through the results, the experimental group has risen more than the controlled one, as well as the effect of the exercises of concentration and attention, which clearly appeared. 2. The proposed exercises have an effective factor in developing the coordination and the relationship between the movement of the hand and the concentration of the attention system.3. And it was very clear among the members of the experimental group through the correct concentration for the kinetic changes.4. The development of the concentration of attention has participated in developing and promoting physical and psychological implementation.Recommendations:1. The training program must include exercises of concentrating attention that are based on the coaches.2. Developing the other physical features for the purpose of achieving the physical and psychological completion for the boxer and to fix the professional execution.3. In the case of training on developing concentrating attention, it mustn't disregard other physical characteristics that affect the right application for concentrating attention.4. Finally, confirming the development of concentrating attention for the boxer will strengthen his own professional implementation; that is why it must concentrate on this aspect.